ANALISIS KELAYAKAN INVESTASI DALAM RANGKA EKSPANSI (STUDI KASUS PADA PDAM TIRTA SATRIA KABUPATEN BANYUMAS) - Nofiyanti, Nofa; Sunarko, Bambang; Widiastuti, Ekaningtyas (Faculty of Economics and Business Universitas Jenderal Soedirman, 2016)
This research study is a case study conducted in PDAM Tirta Satria Kabupaten Banyumas. This research entitled “Invesment Feasibility Analysis in the Context Ex-pansion (Case Study of PDAM Tirta Satria Kabupaten Banyumas)”. The objective of this research study is to determine the expansion in fixed assets that will conducted by PDAM Tirta Satria Kabupaten Banyumas feasible in the term of Internal Rate of Return (IRR) and Payback Period methods. Population and sample in this research is PDAM Tirta Satria Kabupaten Banyumas, using boring sampling as a sampling method.The result of the research showed: the investment in order to expand the addition of fixed assets that will be run by PDAM Tirta Satria Kabupaten Banyumas feasible by considering the results of the analysis Internal Rate of Return method of 21% which greater than the cost of capital that has been determined of 10% (IRR>k) and Payback Period method, the investment will show a time for 4 years and 8 months 26 days to capital return on investment so that investment is feasible.